Pengaruh Budaya Kerja, dan Kompetensi terhadap Kinerja Pegawai Dinas Perdagangan dan Perindustrian Kabupaten Bogor dan Etos Kerja Sebagai Variabel Intervening - Heri Hepriadi; Besar Agung Martono (Syntax Idea)
The Bogor Regency Trade and Industry Office is tasked with managing trade and industry in the area with the aim of enhancing economic competitiveness. However, the performance of employees in the office has not been optimal. This study aims to evaluate the influence of work culture and competence on the performance of employees of the Bogor Regency Trade and Industry Office, with work ethic as a variable that acts as a mediator. A sample of 112 respondents out of a total of 154 employees was selected using the Slovin formula. Data were collected through questionnaires and direct observation, then analyzed using the Smart Partial Least Square (PLS) method version 3.0 as well as reliability, validity, statistical, and classical assumption tests. The results show the influence of work culture and competence on employee performance, the influence of work culture on work ethic, the influence of competence on work ethic, the influence of work ethic on employee performance, as well as the influence of work culture and competence on employee performance through work ethic as a mediator variable.